Towards precision nanomedicine for cerebrovascular diseases with emphasis on Cerebral Cavernous Malformation (CCM). (3rd July 2021) - Perrelli, Andrea; Fatehbasharzad, Parisa; Benedetti, Valerio; Ferraris, Chiara; Fontanella, Marco; De Luca, Elisa; Moglianetti, Mauro; Battaglia, Luigi; Retta, Saverio Francesco
ABSTRACT: Introduction : Cerebrovascular diseases encompass various disorders of the brain vasculature, such as ischemic/hemorrhagic strokes, aneurysms, and vascular malformations, also affecting the central nervous system leading to a large variety of transient or permanent neurological disorders. They represent major causes of mortality and long-term disability worldwide, and some of them can be inherited, including Cerebral Cavernous Malformation (CCM), an autosomal dominant cerebrovascular disease linked to mutations in CCM1/KRIT1, CCM2, or CCM3/PDCD10 genes. Areas covered : Besides marked clinical and etiological heterogeneity, some commonalities are emerging among distinct cerebrovascular diseases, including key pathogenetic roles of oxidative stress and inflammation, which are increasingly recognized as major disease hallmarks and therapeutic targets. This review provides a comprehensive overview of the different clinical features and common pathogenetic determinants of cerebrovascular diseases, highlighting major challenges, including the pressing need for new diagnostic and therapeutic strategies, and focusing on emerging innovative features and promising benefits of nanomedicine strategies for early detection and targeted treatment of such diseases. Expert opinion : Specifically, we describe and discuss the multiple physico-chemical features and unique biological advantages of nanosystems, including nanodiagnostics, nanotherapeutics, and nanotheranostics, that may help improving diagnosis and treatment of cerebrovascular diseases and neurological comorbidities, with an emphasis on CCM disease.